Coping strategies modify risk of depression associated with hematopoietic cell transplant symptomatology. (July 2018) - Barata, Anna; Gonzalez, Brian D; Sutton, Steven K; Small, Brent J; Jacobsen, Paul B; Field, Teresa; Fernandez, Hugo; Jim, Heather SL
To determine whether coping strategies modify the risk of depression among allogeneic recipients experiencing post-transplant-related symptomatology, 105 participants (mean age = 52 years, 42% female) completed questionnaires 90 days post-transplant. A total of 28 percent reported depressive symptoms. Univariate correlations indicated that depression was associated with greater transplant-related symptomatology and avoidance, acceptance/resignation, and emotional discharge coping. Depression was negatively associated with problem-solving coping. Moderator analyses indicated that transplant-related symptomatology was significantly associated with depression among patients who frequently used maladaptive coping and rarely used adaptive coping. These data suggest that transplant-related symptomatology, combined with maladaptive coping, place patients at risk of depression.